2015
DOI: 10.4155/bio.14.312
|View full text |Cite
|
Sign up to set email alerts
|

Hplc–MS/MS Method for The Determination of Four Lignans from Phyllanthus Urinaria L. in Rat Plasma and its Application

Abstract: The HPLC-MS/MS method was successfully applied to a PK study of the four lignans in rats after oral administration of Phyllanthus urinaria L. extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The spectra showed the presence of sodium adduct [M + Na] + ions as molecular ions for all lignans when utilising electrospray ionisation (ESI) positive ionisation mode. Hypophyllanthin did not produce protonated adduct [M + H] + ions while the ions were produced at a low level for phyllanthin ( Fan et al, 2015 ). In another study, metabolite changes of aqueous ethanol extracts of P. niruri were determined by using a proton nuclear magnetic resonance ( 1 H-NMR)-based metabolomics approach.…”
Section: Isolation Qualitative and Quantitative Analyses Of Hypophyll...mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra showed the presence of sodium adduct [M + Na] + ions as molecular ions for all lignans when utilising electrospray ionisation (ESI) positive ionisation mode. Hypophyllanthin did not produce protonated adduct [M + H] + ions while the ions were produced at a low level for phyllanthin ( Fan et al, 2015 ). In another study, metabolite changes of aqueous ethanol extracts of P. niruri were determined by using a proton nuclear magnetic resonance ( 1 H-NMR)-based metabolomics approach.…”
Section: Isolation Qualitative and Quantitative Analyses Of Hypophyll...mentioning
confidence: 99%
“…The partial least-square (PLS) results showed that the phytochemicals, including hypophyllanthin were correlated with antioxidant and α-glucosidase inhibitory activities of the extracts, which were higher in the sample material extracted with 80% ethanol ( Mediani et al, 2017 ). Table 1 shows the summary of qualitative or quantitative of hypophyllanthin in Phyllanthus species such as P. amarus ( Somanabandhu et al, 1993 ; Tripathi et al, 2006 ; Srivastava et al, 2008 ; Inchoo et al, 2011 ; Ilangkovan et al, 2013 ; Kandhare et al, 2013 ; Sukhaphirom et al, 2013 ; Parvathaneni et al, 2014a ; Kumar et al, 2015 ; Pradit et al, 2015 ; Kumar et al, 2017 ), P. niruri ( Hussain et al, 1995 ; Murugaiyah and Chan 2006 ; Murugaiyah and Chan 2007a ; Murugaiyah and Chan 2007b ; Murugaiyah and Chan 2009 ; Jantan et al, 2014 ; Kumar et al, 2017 ; Mediani et al, 2017 ) , P. urinaria ( Ilangkovan et al, 2013 ; Van Thanh et al, 2014 ; Fan et al, 2015 ) , P. maderaspatensis L. ( Srivastava et al, 2008 ), and P. virgatus G. Forst. ( Srivastava et al, 2008 ).…”
Section: Isolation Qualitative and Quantitative Analyses Of Hypophyll...mentioning
confidence: 99%